Numerical method for solving multipoints elliptic-parabolic equation for dehydration process - Saipan@Saipol, Hafizah Farhah (2012)
Drying is the oldest and efficient form of preserving fruits. This research focuses on the mathematical modeling of tropical fruits dehydration using instant controlled pressure drop (Détente Instantanée Controlée or known as DIC) technique. We proposed a modification of mathematical modeling to enhance the previous modeling from Haddad et al. [10]. The mathematical modeling presents the dehydration process of DIC technique which involves parameters such as pressure, water content, time dependency, dimension of region and temperature behavior. The modification of the mathematical modeling has been done by transforming the quadratic equation to partial differential equation (PDE). The simulation of the dehydration process will be illustrated through Jacobi method based on two, three and five points forward difference schemes. The sequential algorithm is developed by using Matlab 7.6.0 (R2008a) programming. The numerical analysis of finite difference schemes in terms of number of iteration, time execution, maximum error and computational cost are compared.